Eutectic growth kinetics and microscopic mechanical properties of rapidly solidified CoCrFeNiMo0.8 high entropy alloy. (15th September 2022) - Yan, P.X.; Chang, J.; Wang, W.L.; Zhu, X.N.; Lin, M.J.; Wei, B.
Abstract: Liquid CoCrFeNiMo0.8 high entropy alloy (HEA) was undercooled by up to 205 K and thus rapidly solidified with electromagnetic levitation technique. A kinetics transition from slow lamellar eutectic growth to rapid anomalous eutectic growth was observed, which showed a significant effect on crystal orientation and mechanical properties. At small undercoolings below 89 K only (σ-CrFeMo + FCC) lamellar eutectic growth proceeded. Once the undercooling exceeded this threshold, anomalous eutectic would grow directly and lead to an extra recalescence peak. The maximum growth velocity of lamellar eutectic was measured as 0.012 m s −1, whereas that of anomalous eutectic attained 2.547 m s −1 at the largest undercooling of 205 K. It was revealed that the eutectic growth mechanism transition resulted from the independent nucleation and cooperative branched growth of the two eutectic phases. An orientation relationship (OR) of 110σ // 111FCC and <111>σ // <110>FCC was determined between σ-CrFeMo and FCC phases by electron backscatter diffraction (EBSD) orientation analysis. Furthermore, mechanical measurements indicated that the hardness, compression strength and ductility of this HEA showed an increasing trend with the rise of liquid undercooling, which may be attributed to structural refinement and the volume fraction increase of anomalous eutectic. Graphical abstract: Image, graphical abstract